DETERMINING THE INTERACTION BETWEEN THE RIO GRANDE AND RIVERSIDE DRAINS USING AN ADCP. (12th November 2012) - Kinzli, K.; Shafike, N.; Manana, N.; Spelman, D.; Roark, M.
ABSTRACT The Middle Rio Grande (MRG), located in central New Mexico, is a river that has experienced significant anthropomorphic changes and requires extensive river management to meet all demands for water. To better understand and manage the MRG, the Upper Rio Grande Water Operations Model was developed by several government agencies; however, drain accretion rates, total seepage volumes from the river to the drain network, and salinity were unknown and represented a large data gap. In 2010, a study using an Acoustic Doppler Current Profiler was conducted to determine drain accretion rates throughout the MRG valley. The use of an Acoustic Doppler Current Profiler allowed for a multitude of measurements to be completed in a short‐time span. The total yearly baseline drain accretion determined during the study was 269 630 AF, which represents about 59% of the water that is diverted annually in the MRG. The magnitude of the drain accretion was much higher than expected and represents a tangible water volume that needs to be addressed in water accounting and management decisions. The New Mexico Interstate Stream Commission is currently using the collected data to improve Upper Rio Grande Water Operations Model and results from the study will aid the Middle Rio Grande Conservancy District in improving water delivery operations. The findings of this study indicate that a complex groundwater, drain, and river water interaction is taking place near the San Acacia diversion dam with upwelling saline groundwater increasing drain water salinity to levels as high as 1703 μS. Further detailed study of groundwater and river water interactions is suggested in this area. Copyright © 2012 John Wiley & Sons, Ltd.